Pemberdayaan Industri Perikanan Madura Melalui Pengembangan Budidaya Laut - Arisandi, Apri; Rokhmaniati, Siti (Universitas Trunojoyo Madura, 2008)
Indonesian as marine continent endowed with vast marine resources, in actual facttwo third of Indonesian territory are sea. Merinefisheries, particularl y capturefisheries, is one of the mine effort to make the most of marine resources for supporting economic development in the country. Overfishing then become the mine concern of thegovernment of Indonesian in marine resource utilization. The data reflects that the exploitation of the resources is approaching the Maximum Sustainable Yield (MSY), especially of the small pelagic fish. Considering theproblems of overexploitation, it is therefore significant todevelop marinefish farming (marine aquaculture or mariculture) as an alternative. Theactivities in mariculture is mainly farming fishes and plant of high value on export market such as Grouper (ikan kerapu) and Seaweed (Rumput laut), but the development of tnariculture in Indonesia is still not as expected. The investor still hesitate to. enter this business because they still feel unsecure due to lack of law and regulations concerning the use of sea waters for mariculture activities. Theconcept of